Peran Job Satisfaction sebagai Pemediasi Pengaruh Talent Management terhadap Workforce Agility (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to empirically test the role of job satisfaction as a mediator of the influence of talent management on workforce agility. The study was conducted on employees of several digital companies that utilize digital technology to create new products and services, improve operational efficiency, and provide a better experience to customers. The research area is in the Special Region of Yogyakarta with 100 respondents obtained through purposive sampling. The analysis method used is Structural Equation Modeling-SmartPLS 4.0. The results of the study indicate that talent management has a direct positive and significant effect on job satisfaction; talent management also has a direct positive and significant effect on workforce agility; while job satisfaction has a direct effect on workforce agility. The results also prove that job satisfaction mediates the effect of talent management on workforce agility but is weaker when compared to its direct effect